Management of Peripheral and Truncal Venous Injuries - Giannakopoulos, Triantafillos G.; Avgerinos, Efthymios D. (Frontiers in Surgery, 2017)
Civilian injuries are increasing according to the World Health Organization, and this is attributed mainly to road traffic accidents and urban interpersonal violence. Vascular injuries are common in these scenarios and are associated with high morbidity and mortality rates. Associated peripheral venous trauma is less likely to lead to death and controversy remains whether ligation or repair should be the primary approach. Conversely, non-compressible truncal venous insult can be lethal due to exsanguination, thus a high index of suspicion is crucial. Operative management is demanding with fair results but recent endovascular adjuncts demonstrate promising results and seem to be the way forward for these serious conditions.